Menjelajahi Faktor-Faktor Pendorong Niat Berkelanjutan untuk Menggunakan Layanan Pemerintah Seluler: Studi Kasus di Indonesia - Taufan Hunneman; Darmawan Napitupulu (Research and Development Agency Ministry of Home Affairs, 2025)
The sustained use of technology is pivotal for ensuring the enduring impact of innovations and improving the quality of services within organizations. The long-term success of Information System (IS)/Information Technology (IT) initiatives hinges not merely on their initial adoption but on their continued use. Therefore, understanding the factors that motivate users to consistently engage with new technologies is essential for evaluating the success and sustainability of such projects. Despite this importance, most research in this domain has primarily focused on user acceptance rather than continued usage. This study aims to bridge this gap by exploring how citizens’ perceptions of usefulness and satisfaction influence their intention to continue using mobile government services. A survey was conducted with 254 Indonesian citizens who had interacted with mobile government platforms. The analysis was performed using Partial Least Squares Structural Equation Modelling (PLS-SEM), with three primary constructs measured: perceived usefulness, satisfaction, and continuance intention to use m-government services. The R² value of the structural model indicates that 83.6% of the variation in continuance intention to use m-government services is explained by perceived usefulness and satisfaction. The findings reveal that perceived usefulness exerts a more substantial influence on continuance intention than satisfaction. The theoretical contribution of this study enhances the understanding of the factors influencing continued use within the context of m-government, while the practical contribution provides insights for policymakers to design more effective and engaging m-government services.